Moebiusov sindrom in anestezija - klinični primer - Šervicl-Kuchler, Darja (Zdravniški vestnik, 2005)
Background. Moebius syndrome is a congenital disorder involving the 6th and 7th cerebral nerves. It very often involves facial and limb anomalies, and thechildren with this disorder can be mentally retarded. Reasons for Moebius syndrome are various and not fully understood. Children with this disease undergo a lot of corrective surgery that requires anaesthesia. Due to their facial anomalies, we have to expect intubation difficulties with these patients. Material and methods. This clinical case report presents a 21-month-old girl with Moebius syndrome who underwent surgery for clubfoot correction under general anaesthesia. We expected difficult airways, and the child also had a history of complications during anaesthesia. During the induction of anaesthesia we encountered a complication associated with the regurgitation of tea. This occurred even though she had not eaten or drunk that day. After a successful intubation with a fibre-optic bronchoscope the surgery was successfully completed. Conclusions. When dealing with a Moebius-syndrome patient, we have to expect a difficult intubation because of the numerous problems associated with this syndrome. We successfully intubatedour patient with a fibre-optic bronchoscope. What we did not expect was the regurgitation of tea from the stomach. In related literature we did not find any data about delayed gastric emptying.
Keywords: Abnormalities; Anestezija splošna; Anesthesia, General; Bronchoscopy; Bronhoskopija; Clubfoot; Dojenček; Facial Bones; Facial Paralysis; Facialna paraliza; Gastroesophageal Reflux; Gastroezofagealni refluks; Infant; Intubacija intratrahealna; Intubation, Intratracheal; Kepasta noga; Obrazne kosti; Surgery